Ecology and biology of the commercially valuable freshwater Asian swamp eel, Monopterus albus - Sow, Ai Yin; Ismail, Ahmad; Zulkifli, Syaizwan Zahmir; Azmai, Mohammad Noor Amal; Hambali, Kamarul (Malaysian Nature Society’s, 2018)
Asian swamp eel, Monopterus albus (Synbranchidae), a sex reversal, air-breathing and eel-like exotic fish is common in freshwater area of the East and Southeast Asia, and even has been reported in Florida waters in 1997. This fish is easily found in paddy fields, ponds, rivers and swampy areas. People, especially farmers, acknowledge it important for protein sources and culture. It is also tasteful, nutritionally rich and medicinally valuable fish with high export demands. However, due to several reasons especially overfishing, its population showed decline and could be potentially classified as a threatened species by IUCN in future. This manuscript will describe its ecological niche and potential for aquaculture activities.